Polisemi Pada Kosakata Anggota Tubuh dalam Bahasa Arab - Oman Karya Suhada (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The purpose of this study was to determine the meaning of polysemy in the vocabulary of limbs in Arabic. This study uses a descriptive method with a content analysis model, while the data source is Arabic vocabulary taken from mu'jam siyaaqi li al-Kalimat al-Sya'iyah by Mahmud Ismail Shinni and Mu'jam al-lughah al-Arabiyah al -mu'ashiroh by Ahmad Mukhtar Umar. The conclusion of this study is that some of the vocabulary of limbs in Arabic has polysemy meanings, including; 1). means teeth, age. 2). means; nose, desireless, contemptible, natural, conceited. 3). means; eyes, spies, treasures, wellsprings, alone, mindful, cash, similar/balanced, real, perishable, happy, popular, envious. 4). لسان means; verbal, spokesperson, argumentation, behavior, hypocrisy, language. 5). means; head, tail, new year, leader, science, birthplace. 6). means; hand, help, kindness, will, cash, giver, receiver, guidance. 7). لب means: heart, in, Yasin's letter, 8). means: chest, beginning, leader, heart. 9). means; breasts, struggle, sacrifice, Self-preservation from obtaining wealth in a bad way, 10). means: face, beginning, self, not feeling humiliated, right, actually, at all, substance, apostasy, equality, 11). means: neck, slave, soul/someone, 12). ل means: foot, soldier, 13). means: back, memorized, thorough, hostility, 14).: feet, forgive, ignore and turn away from him, may Allah strengthen his heart, make mistakes, the same, all strength, perfect, start working, rise from adversity, high position, 30 CM. All of these meanings will be understandable if used in the context of a sentence.